The effects of airflow on oven temperatures and cakes qualities - Mohamad Shahapuzi, Nur Syafikah; Taip, Farah Saleena; Ab. Aziz, Norashikin; Ahmedov, Anvarjon (Universiti Putra Malaysia Press, 2015)
The presence of airflow during heating process is expected to increase heat uniformity in a closed heating chamber. Circulation of hot air increases the percentage of convective heat transfer. In this study, effects of airflow on oven temperature, cake temperature and several cake qualities were investigated. Experimental studies were conducted in convective oven using two different baking modes; with and without airflow. During baking, oven temperatures and internal cake temperature were measured, and images of cake expansion were captured. Results of the study showed that the presence of airflow could maintain the oven temperature within a small range of set point temperature. Temperature in the oven exhibited ±5.5°C fluctuation, approximately 3.5% overshoot that occurred continuously during baking with airflow. On the contrary, higher overshoot (ranging from 15 to 30%) was observed in oven temperature without airflow. Airflow also showed a significant effect (p<0.01) during the second stage of baking. The presence of airflow increased the heating rate and resulted in a faster volume expansion, which was 3.21mm/min, as compared to 2.88mm/min without the airflow. However, airflow dried off the cake surface, resulted in quicker browning, higher weight loss and lower moisture content of cakes.